Performance of broodstock and hybrid juvenile of Egyptian and sangkuriang Clarias gariepinus strains - Zulfania, Putri; Junior, Muhammad Zairin; Alimuddin, ,; Sunarma, Ade (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT This study was conducted to evaluate reproduction of broodstock and intraspecific hybrid juvenile performance of Egyptian (M) and sangkuriang (S) strain African catfish Clarias gariepinus at nursery phase. Intraspecific hybridization of African catfish was carried out reciprocally (SM and MS) and purebreed (SS and MM), each was with three replicates. Fish spawning was conducted by artificial fertilization, and larvae were reared at 1st, 2nd and 3rd nursery phases, subsequently. The results showed that broodstock performance (male and female) of both strains were not significantly different (P>0.05) on all reproduction traits, except female’s gonadosomatic index. Fertilization and hatching rates of all hybrids were not significantly different (P>0.05). MM juvenile had higher growth performances than other juvenile hybrids. Heterosis of total length, standard length, and body weight were varied, whereas the survival showed positive heterosis. SM juvenile showed positive growth heterosis in 3rd nursery phase (total length, standard length, and body weight were 2.61%; 2.16%, and 4.79% respectively). Survival heterosis of MS juvenile (24.20% for total length; 103.13% for standard length and 11.62% body weight) was higher than SM juvenile (6.86%; 48.57%, and 3.09%) on all nursery phases Keywords: African catfish, intraspecific hybridization, growth, survival, heterosis ABSTRAK Penelitian ini dilakukan untuk menguji performa reproduksi induk dan benih hasil hibridisasi intraspesifik ikan lele Afrika Clarias gariepinus strain Sangkuriang (S) dan Mesir (M) pada fase pendederan. Hibridisasi intraspesifik ikan lele Afrika dilakukan secara resiprokal (SM dan MS) dan galur murni (SS dan MM) masing-masing dengan tiga ulangan. Pemijahan dilakukan secara buatan dan larva yang dihasilkan dipelihara pada fase pendederan pertama, kedua, dan ketiga. Hasil penelitian menunjukkan bahwa performa induk ikan lele jantan dan betina pada kedua strain tidak berbeda nyata (P>0,05) pada seluruh parameter reproduksi, kecuali indeks gonadosomatik (GSI) pada induk betina. Derajat pembuahan dan penetasan telur pada seluruh persilangan tidak berbeda nyata (P>0,05). Pertumbuhan benih persilangan MM lebih tinggi, dibandingkan benih hasil persilangan lain. Nilai heterosis panjang total, panjang standar, dan bobot tubuh yang dihasilkan pada setiap stadia pendederan bervariasi, sedangkan nilai heterosis kelangsungan hidup menunjukkan hasil seluruhnya positif dibandingkan rataan galur murni. Heterosis pertumbuhan benih persilangan SM pada pendederan ketiga menunjukkan hasil yang positif (2,61% untuk panjang total; 2,16% untuk panjang standar dan 4,79% untuk bobot tubuh). Nilai heterosis kelangsungan hidup benih persilangan MS (24,20% untuk panjang total; 103,13% untuk panjang standar dan 11,62% untuk bobot tubuh) lebih tinggi dibandingkan benih persilangan SM (6,86%, 48,57% dan 3,09%) pada setiap stadia pendederan. Kata kunci: ikan lele Afrika, hibridisasi intraspesifik, pertumbuhan, kelangsungan hidup, heterosis